ANALISIS NILAI PROFIL PELAJAR PANCASILA PADA CERITA PENDEK DALAM BUKU BAHASA INDONESIA LIHAT SEKITAR KELAS IV SDN 2 PANGENREJO - Raysita Cahya Anggraeni; Arun Ratnaningsih; Muflikhul Khaq (Jurnal Binagogik, 2024)
This research aims to analyze the profile value of Pancasila students in short stories in the Indonesian language book Look Around for class IV at SD N 2 Pangenrejo. The type of research used is qualitative research. The data collection techniques used in this research were observation, interviews, documentation and data cards. The instrument of this research is a data card. The data analysis techniques used were data collection, data reduction, data presentation and data verification. The research results showed that there were 28 Pancasila student profile character values ​​in short stories. The short stories with the most Pancasila student profile scores are "Likes and Dislikes" and "Good Cooperation" with 5 Pancasila student profile scores. The short stories entitled "Chief of the Len Tribe", "Strong to Protect", "In Exchange for What?", and "Garuk-Garuk" are 3 values ​​for the profile of Pancasila students. The short stories entitled "No Longer Fit", "Adventure in the Savanna of Sumba", and "Wrong Shoes" are 2 values ​​for the Pancasila student profile. The Pancasila student profile values ​​that emerge are personal moral values, morals towards nature, knowing and appreciating culture, communication and intercultural interaction, collaboration, sharing, understanding oneself and the situation one faces, self-regulation, obtaining and processing information and ideas, analyzing and evaluate reasoning, reflect and evaluate one's own thoughts, produce original ideas, produce original works and actions, have flexibility in thinking in finding alternative solutions to problems.